ANALISIS KESULITAN BELAJAR PADA MATERI OPERASI HITUNG PEMBAGIAN DI SD - Yuliana, Erika; Purnamasari, Iin; Purnamasari, Veryliana (Elementary School Teacher and Education (PGSD), Faculty of Teacher Training and Education, 2020)
This research to determined the difficulty of learning in the calculation of the operation material at elementary school. The background this research is the importance of understanding the devide operations as a basis for learning mathematics. This research was a qualitative and precentage research. The result showed the difficulty of learning the devide operations includes difficulties in understanding the concept of division and difficulty inusing the principle of division; the factors that influence the learning difficulties of devide operations consists of internal factors, namely motivation, interest, and attention, while the external factors are teaching methods, teacher relations with students, and giving reinforcement feedback; a solution to overcome learning on material of devide operations that is learning with methods that are adapted to the conditions of students in order to increase motivation, interst, and attention of students in learning the devide operations, learning is carried out according to the learning steps according to Piaget?s theory and using the block dienes